2017
DOI: 10.1016/j.jclepro.2016.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic impact assessment of China's CO2 emissions peak prior to 2030

Abstract: Abstract:China is the largest emitter of carbon emissions in the world. In this paper, we present an Integrated Model of Economy and Climate (IMEC), an optimization model based on the input-output model. The model is designed to assess the tradeoff between emission deceleration and economic growth. Given that China's projected average growth rate will exceed 5% over the next two decades, we find that China may reach its peak CO2 emissions levels by 2026. According to this scenario, China's carbon emissions wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(132 citation statements)
references
References 47 publications
2
129
0
1
Order By: Relevance
“…Meanwhile, we compare the results of other research to those of this paper. In 2017, Mi et al [30] use IMEC (Integrated Model of Economy and Climate) model to do forecasting. They say China will reach an emission peak at 11.20 Gt (1Gt = 1 × 10 9 tons) in 2026.…”
Section: Alds Mixture Model Vs Qr and Cqrmentioning
confidence: 99%
“…Meanwhile, we compare the results of other research to those of this paper. In 2017, Mi et al [30] use IMEC (Integrated Model of Economy and Climate) model to do forecasting. They say China will reach an emission peak at 11.20 Gt (1Gt = 1 × 10 9 tons) in 2026.…”
Section: Alds Mixture Model Vs Qr and Cqrmentioning
confidence: 99%
“…Several authors have questioned Chinese energy and carbon data and revealed that energy consumption in China was underestimated by the Chinese national statistics while its carbon emissions were overestimated by the IPCC and other reports [46][47][48]. The gap between them also affects the results.…”
Section: Uncertainty Analysismentioning
confidence: 99%
“…The details of lower calorific value, carbon emissions factors and oxidation rate have been reported in previous literature [49,50].…”
Section: Estimation Of Energy-related Carbon Emissionsmentioning
confidence: 97%